2007
DOI: 10.1007/bf03403728
|View full text |Cite
|
Sign up to set email alerts
|

Non-communicable Disease and Injury-related Mortality in Rural and Urban Places of Residence: A Comparison between Canada and Australia

Abstract: Background: Few published studies looking at cross-national comparisons of rural-urban health status are available. As a first step towards addressing the lack of information on how rural populations in Canada compare with rural populations elsewhere in the world, this paper examines and contrasts Canadian mortality risks of selected diseases in rural and urban areas with those of Australia. Methods: Age-standardized mortality ratios for selected causes of deaths were calculated at the national level and broke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 25 publications
8
30
0
Order By: Relevance
“…Consistent with our study, excess lung cancer mortality in rural areas was found for Australia during 1997–1999 [60]. All-cancer and lung cancer mortality rates for Canadian men and women during the period 1986–1996 were lower in rural than in urban areas [60]. In many European countries (such as Denmark, Spain, Germany, and Italy) that have relatively high lung cancer mortality rates, smoking prevalence tends to be higher in urban than in rural areas, which may imply significantly higher lung cancer mortality risks among their urban residents [61].…”
Section: Part Isupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with our study, excess lung cancer mortality in rural areas was found for Australia during 1997–1999 [60]. All-cancer and lung cancer mortality rates for Canadian men and women during the period 1986–1996 were lower in rural than in urban areas [60]. In many European countries (such as Denmark, Spain, Germany, and Italy) that have relatively high lung cancer mortality rates, smoking prevalence tends to be higher in urban than in rural areas, which may imply significantly higher lung cancer mortality risks among their urban residents [61].…”
Section: Part Isupporting
confidence: 90%
“…Consistent with our study, excess lung cancer mortality in rural areas was found for Australia during 1997–1999 [60]. All-cancer and lung cancer mortality rates for Canadian men and women during the period 1986–1996 were lower in rural than in urban areas [60].…”
Section: Part Isupporting
confidence: 87%
See 1 more Smart Citation
“…Disparities in injury rates by income quintiles and by urban and rural areas suggest that motor vehicle traffic injuries are related to the environments in which children live. Similar to other international studies, rates of vehicle occupant injury were higher in rural than in urban areas 23 24 39. These higher rates may reflect greater travel distances, less safe driving conditions, and reduced access to emergency services in rural areas.…”
Section: Discussionsupporting
confidence: 80%
“…Previous reports have also found that cancer mortality is worse among lung, prostate, and colorectal cancer patients residing in rural versus urban Canada [2,7]. Similar observations have been reported in the United States and Australia [7–9]. …”
Section: Introductionsupporting
confidence: 78%